Discharge Before Return to Respiratory Baseline in Children With Neurologic Impairment. Issue 9 (20th May 2020) - Steuart, Rebecca; Tan, Rachel; Melink, Katherine; Chinchilla, Sofia; Warniment, Amanda; Shah, Samir S; Thomson, Joanna
Abstract : BACKGROUND: Children with neurologic impairment (NI) are commonly hospitalized with acute respiratory infections (ARI). These children frequently require respiratory support at baseline and are often discharged before return to respiratory baseline. OBJECTIVE: To determine if discharge before return to respiratory baseline is associated with reutilization among children with NI hospitalized with ARI. METHODS: This single‐center retrospective cohort study included children with NI aged 1 to 18 years hospitalized with ARI who required increased respiratory support between January 2010 and September 2015. The primary exposure was discharge before return to respiratory baseline. The primary outcome was 30‐day hospital reutilization. A generalized estimating equation was used to examine the association between exposure and outcome while accounting for within‐patient clustering and patient‐level clinical complexity and illness severity. RESULTS: In the 632 hospitalizations experienced by 366 children, children were discharged before return to respiratory baseline in 30.4% of hospitalizations. Compared with those hospitalizations in which children were discharged at baseline, hospitalizations with a discharge before return to respiratory baseline were more likely to be for privately insured, technology‐dependent children with respiratory comorbidities. Compared with discharges at respiratory baseline, discharges with increased respiratory support had no difference in 30‐day reutilization (32.8% vs 31.8%; P = .81; adjusted OR 0.80, 95% CI 0.51‐1.26). CONCLUSIONS: Among children with NI hospitalized with ARI, discharge before return to respiratory baseline was common, but it was not associated with hospital reutilization. Return to respiratory baseline may not be a necessary component of discharge criteria in this population. Abstract :